Editorial - Dewaele, Jean-Marc; Li, Chengchen (Studies in Second Language Learning and Teaching, 2018)
This is the first special issue devoted specifically to emotions in second language acquisition (SLA). Influenced by the positive psychology movement (Fredrickson, 2001), there has been a shift away from an exclusive focus on negative emotions in SLA to a more holistic analysis of both negative and positive emotions among learners (Dewaele & MacIntyre, 2014; MacIntyre & Gregersen, 2012; MacIntyre, Gregersen, & Mercer, 2016; MacIntyre & Mercer, 2014). We are not claiming that nobody had considered positive emotions and affect in SLA before 2012, as indeed many researchers prepared the ground (e.g., Arnold, 1999; Broner & Tarone, 2001; Cook, 2000; Dewaele, 2005; Kramsch, 2006). Moreover, educational psychologists did point to the pivotal role of positive academic emotions that sustain motivation (Pekrun, 1988, 2014; Pekrun, Goetz, Titz, & Perry, 2002a, 2002b). However, none of the SLA studies created the kind of wave of interest in emotions in SLA that we are currently witnessing. It is possible that now the time is ripe, as the success of the biennial Psychology of Language Learning conferences illustrates, as well as the establishment of the new International Association of Psychology of Language Learning during the second conference in Finland in 2016.